Book review: Guerrini, Mauro. From cataloguing to metadata creation: a cultural and methodological introduction - Maceviciute, Elena (Information Research an international electronic journal, 2023)
Guerrini, Mauro. From cataloguing to metadata creation: a cultural and methodological introduction. London: Facet Publishing, 2023. xxiv, 128 p. ISBN 978-1-78330-628-2